Kebijakan Kepala Madrasah Dalam Mendukung Pendidikan Kepramukaan di MTS NU Aswaja Tengaran Kab. Semarang - Suroya, Lu’luk; Yasin, Ahmad (Attractive : Innovative Education Journal, 2020)
This research is an effort to find out the madrasa head's policy in supporting Scouting education in MTs NU Aswaja Tengaran. To explore and collect data in this study, researchers used a descriptive qualitative approach with observation, interview and documentation studies as well as data reduction techniques. In this study shows that the scout extracurricular has existed since the inception of the NTS Aswaja Tengaran MTS as an effort in shaping the character of students who have noble character. In addition, there is a new regulation in the form of Permendikbud No. 63 of 2014 concerning Scouting Education which is one of the reasons for Scout extracurricular activities at MTs NU Aswaja Tengaran. With this regulation, the school can perform Scout extracurricular activities better. In addition, school principals supporting scouting education activities have a positive influence and also aligning scouting education and Islamic religious education, which has a role in the character education of students. Keywords: Policy, Head/Madrasa, Scouting Education.